OC-014 Dietary oleic acid protects against the development of ulcerative colitis: a UK prospective cohort study using data from food diaries. (23rd September 2015) - de Silva, P S A; Luben, R; Shrestha, S S; Welch, A; Khaw, K; Hart, A R
Abstract : Introduction: Dietary factors, including fatty acids, may be involved in the aetiology of ulcerative colitis (UC). Oleic acid (C18:1 cis 9), an n-9 monounsaturated fatty acid (n-9 MUFA) is found in high amounts in olive and grapeseed oils and inhibits the formation of pro-inflammatory metabolites which are found in high concentrations in the mucosa of patients with UC. The aim of this study was to investigate, for the first time in a prospective cohort study, the effect of dietary oleic acid on the risk of ulcerative colitis. Methods: A total of 25 639 men and women aged 40–74 years, from general practices in Norfolk UK, were recruited into EPIC-Norfolk (European Prospective Investigation Into Cancer). At baseline, participants completed detailed 7-day food diaries. These were interpreted by nutritionists, using DINER a specifically designed computer programme containing information on the nutrient content of 9000 food items. The cohort was monitored for participants who subsequently developed incident ulcerative colitis. Each case was matched for age and sex with four controls. Conditional logistic regression was used to calculate the odds ratios for oleic acid and the risk of ulcerative colitis, adjusted for cigarette smoking and also n-3 and n-6 PUFAs which influence the inflammatory process. Results: In the cohort, 22 participants (45% women) developed incident ulcerative colitis after a median follow-up time of 3.9 years (range 1.8–8.3 years). The extent of the inflammation was left-sided, up to the splenic flexure, in 47% of patients. The highest tertile of dietary oleic acid intake was associated with an odds ratio for UC of 0.11 (95% CI 0.01 to 0.87) with a statistically significant protective trend across tertiles (OR 0.33, 95% CI 0.12 to 0.93, p=0.04). The attritutable fraction, the proportion of cases of UC due to the lower intakes of oleic acid, was 46%. Conclusion: The dietary intake of oleic acid was negatively associated with the development of UC. If this is a causal association, then increasing the dietary intake of oleic acid may prevent UC. Oleic acid supplementation could be a possible treatment for patients with this illness.